Timing of RRT initiation in critically-ill patients: time for precision medicine - Kipnis, Eric; Garzotto, Francesco; Ronco, Claudio (Journal of Thoracic Disease, 2016)
Recently published randomized controlled trials have brought a focus upon the timing of renal replacement therapy (RRT) initiation in critically-ill patients (1,2). The AKIKI study randomized 620 ICU patients with severe acute kidney injury (AKI) [kidney disease improving global outcomes (KDIGO) classification, stage 3] to either immediate initiation of RRT or delayed initiation according to predetermined mandatory RRT criteria (1). Gaudry et al. found no significant difference in mortality between early and delayed RRT initiation strategies in critically-ill patients results, suggesting that careful monitoring of patients for predetermined mandatory RRT criteria may safely allow delaying RRT in ventilated and/or catecholamine-dependent patients with severe AKI.